Comparison of Fathers' Perceptions of Gender Roles and Their Impact on Breastfeeding Support in the Turkish Population: A Cross‐Sectional Study. - Öztürk, Simge; Timur Taşhan, Sermin; Sampaio, Francisco (Perspectives in Psychiatric Care, 2025)
Purpose: This study aims to determine the impact of fathers' perceptions of gender roles on breastfeeding support in the Turkish population. Methods: This cross‐sectional, descriptive, and correlational design study was conducted with fathers of infants aged 0–6 months (n = 502) who were followed up at the pediatric outpatient clinics of a state hospital in Turkey between September and October 2024. Data were collected using the Personal Information Form, the Partner Breastfeeding Influence Scale, and the Gender Perception Scale. Analyses included percentages, means, standard deviations, one‐way ANOVA, independent samples t‐test, Kruskal–Wallis, Mann–Whitney U, Pearson Correlation, and path analysis. Results: Around nine out of every 10 babies were younger than 4 months old, and half of them were the first breastfed child. Path analysis showed that the father being currently employed (β = −0.34; p < 0.001), having planned the pregnancy (β = −16, p < 0.001), infant's age (β = −13, p < 0.001), and the GPS total score (β = −11, p < 0.05) had a significant effect on the breastfeeding process and explained 17% of the total variance. Conclusion: This study found that the father being currently employed, living in a city center, having a planned pregnancy, the infant's early age, and egalitarian perceptions of gender roles had a positive effect on breastfeeding. When evaluating breastfeeding, healthcare professionals should consider the effects of partner breastfeeding influence and gender perception on breastfeeding.